Palladium‐Catalyzed Aryl Amination Reactions of 6‐Bromo‐ and 6‐Chloropurine Nucleosides - Thomson, Paul F. (WILEY‐VCH Verlag, 2010)
Palladium‐catalyzed C—N bond forming reactions of 6‐bromo‐ as well as 6‐chloropurine ribonucleosides and the 2′‐deoxy analogues with arylamines are described. Efficient conversions were observed with palladium(II) acetate/Xantphos/cesium carbonate, in toluene at 100 °C. Reactions of the bromonucleoside derivatives could be conducted at a lowered catalytic loading [5 mol% Pd(OAc)(2)/7.5 mol% Xantphos], whereas good product yields were obtained with a higher catalyst load [10 mol% Pd(OAc)(2)/15 mol% Xantphos] when the chloro analogue was employed. Among the examples evaluated, silyl protection for the hydroxy groups appears better as compared to acetyl. The methodology has been evaluated via reactions with a variety of arylamines and by synthesis of biologically relevant deoxyadenosine and adenosine dimers. This is the first detailed analysis of aryl amination reactions of 6‐chloropurine nucleosides, and comparison of the two halogenated nucleoside substrates.